Development of blended learning model in numerical method course - Siti Aminah (International Journal on Teaching and Learning Mathematics, 2018)
The aim of this study is to develop a blended learning system with two stay two stray using problem-based learning worksheet. The study is a research and development. The study used four D models covering define, design, development and disseminate stage. Then, the system of the blended learning model and problem-based learning worksheet were validated by two validators with valid criteria and some revisions. For test efficiency, data were processed using a paired sample T-test. The result showed that the average learning outcome improved after the implementation of a blended learning system in which the outcomes of earning significantly improved.